A feline model of spontaneously occurring autoimmune limbic encephalitis - Glantschnigg-Eisl, U; Klang, A; Kneissl, S; Lang, B; Waters, P; Irani, SR; Binks, SNM; Pakozdy, A (Elsevier, 2023)
Autoimmune encephalitis (AE) is an important cause of encephalitis in humans and occurs at a similar rate to infectious encephalitis. It is frequently associated with antibodies against the extracellular domain of neuronal proteins. Among human AE, that with antibodies against leucine-rich glioma-inactivated 1 (LGI1) is one of the most prevalent forms, and was recently described in cats with limbic encephalitis (LE). In this study, we describe a large cohort (n = 32) of cats with AE, tested positive for voltage gated potassium channel (VGKC)-antibodies, of which 26 (81%) harboured LGI1-antibodies. We delineate their clinical and paraclinical features as well as long-term outcomes up to 5 years. Similar to human cases, most cats with LGI1-antibodies had a history of focal seizures (83%), clustering in the majority (88%), with interictal behavioural changes (73%). Among feline AE patients, there was no seizure type or other clinical characteristic that could distinguish LGI1-antibody positive from negative cats, unlike the pathognomic faciobrachial dystonic seizures seen in humans. Although six cats were euthanased in the first year for epilepsy-associated reasons, those attaining at least 1-year survival had good seizure control and quality of life with appropriate veterinary care and medication. Acute-phase immunotherapy (prednisolone) was given to the most severely unwell cases and its effect is retrospectively evaluated in 10 cats. Our data show LGI1-antibodies are an important cause of feline encephalitis, sharing many features with human AE. Further research should examine optimal therapeutic management strategies and the cause of LE in seronegative cats, building on paradigms established in the counterpart human disease.